FAKTOR DETERMINAN YANG MEMPENGARUHI TURNOVER INTENTION - Pangestika, Asri; Yohani, Yohani; Hidayah, Rini (Neraca, 2023)
This study aims to determine what factors influence turnover intention. The target sample for this study is the accounting division employees of the Regional Development Bank (BPD) in the Special Province of Yogyakarta. The number of samples used in this study were 45 respondents. The method of determining the sample in this study used a purposive sampling method. Data collection was carried out using a questionnaire method. The results of this study indicate that job insecurity, job stress, and role conflict have a positive effect on turnover intention. Meanwhile, accounting competence has a negative effect on turnover intention. This study contributes to literature and practice, (1) For management, this research can be used as material for consideration in the management of human resources, namely employees. In addition, this research can be used as a guide to find out how to increase the level of employee loyalty in working effectively and efficiently. (2) For future researchers, this research can be used as a guideline for conducting research in the same field, especially related to the factors that influence the level of turnover intention.